PENILAIAN STATUS GIZI SISWI KELAS X DAN XI DI SMAN 1 DEPOK, KABUPATEN SLEMAN, YOGYAKARTA - Sicilia; Merta Kusuma, Reni (MEDIA ILMU KESEHATAN, 2016)
Background: Teenagers, especially femalearesusceptible to problems related to malnutrition such as Chronic Energy Deficiency (CED). Objective: To determine the characteristics of nutritional status based on age, weight, height, arm circumference, and Body Mass index (BMI) in X and XI grade students at SMAN 1 Depok, Sleman District, Yogyakarta. Method: The study was an observational study with cross-sectional approach. Measurement used a digital scale, mikrotoise, and upper arm circumference tape. Subjects in this study were 250 female teenagers. Descriptivequantitative analysis was employed for data with numerical/continuous scale (ratio and interval). Results: The majority of female teenagers aged between 14-18 years (mean= 16yo). The meanweight was 50.58 kg, the meanheightwas 155.65 cm, and the mean size of the upper-arm circumference was 24.9 cm. The measurement showed the mean BMI was 20.9 kg/m2. Ten percent of students were categorized as severeunderweight (severe CED) and 7.2% were in the obesecategory. Measurement of nutritional status with upper-arm circumference showed 33.6% female teenagerswere at risk of CED. Conclusion: There were female teenagerswho had problems with nutritional status (severe underweight and obese). Upper-arm circumference measurement results showed 33.6% of teenagers were at risk of CED. Keyword: Nutritional status, BMI, upper-arm circumference, CED